Poststroke Aphasia Rehabilitation: Why All Talk and No Action?. (April 2019) - Wortman-Jutt, Susan; Edwards, Dylan
There is ample agreement in the scientific literature, across diverse areas of study, that suggests that language and movement are interrelated. In particular, it is widely held that the upper limb and hand play a key role in language use. Aphasia, a common, disabling language disorder frequently associated with stroke, requires new restorative methods. A combinatorial hand-arm-language paradigm that capitalizes on shared neural networks may therefore prove beneficial for aphasia recovery in stroke patients and requires further exploration.